La Meglio Gioventù: Earnings Gaps across Generations and Skills in Italy - Paolo Naticchioni; Michele Raitano; Claudia Vittori (Institute for the Study of Labor (IZA), 2014)
This paper documents the evolution of the experience-earnings profiles of private employees in Italy over the first six years of working career across three birth cohorts (1965-1969, 1970- 1974, 1975-1979). We explore the average trends and disentangle how the patterns vary according to individual skills, defined in terms of both educational levels and percentiles of the unconditional earnings distribution. Unlike previous studies, and in contrast with the expectations prompted by the skill-biased literature, our results surprisingly show that the Italian best of youth, i.e. the best workers of the most recent cohorts (the high skilled), have suffered, compared to the previous cohorts, an earnings penalty much more severe than that experienced by unskilled workers. This finding also raises questions about the effectiveness of the European Employment Strategy, which repeatedly stressed the importance of human capital and technological knowledge as main drivers for European performance.
Keywords: J24; J31; 330; youth; cohorts; education; earnings; Italy